ANALISA KESALAHAN DALAM PENERJEMAHAN KITAB AL-BALAGAH AL-WADIHAH KARYA ALI AL-JARIM DAN MUSTAFA AMIN - Faiq Ainurrafiq (IAIN Ponorogo, 2015)
Abstract: The overflow of foreign language books and high demands of market with the need of new products, including the translation, makes the quality of translation work has decreased. In this void, a critic on translation is necessary in order to create an atmosphere of critical and dialogical associated with the work of translation. This paper analyzed and discussed errors of translation of the book of al-Balagah al-Wadihah work of Ali al-Jarim and Mustafa Amin. In accord to this, the researcher attempted to know the forms of errors in the results of translation of al-Balagah al-Wadihah, and how the correct form of alternative translation should be. The results showed that the error in the target language sentence structure included the sequence position of sentences. Errors in the use of sentence effectiveness dealt with translating unnecessary text and repetition of words that had been mentioned. Errors in translating vocabulary covered improper equivalent elections, not equivalence of word categories, and inaccuracy of idiom translation. Additionally, errors were also found in the aspect of eliminating vocabulary, phrases, and sentences. ةيعون لىإ ةديدلجا ةجمترلما بتكلا تاجاتنا لىإ قاوسلأا تاجاحو ةيبنجلأا ةغللاب ةيرثكلا بتكلا دورو تّ دأ نع يراولحاو يدقنلا ولجا نيوكت فدهب ىجمترلا دقنلا دوجو لىإ اذه عفدو .ةفيعضو ةلمهم ةجمترلا ةدوجو ىفطصمو مرالجا يلعل « ةحضاولا ةغلابلا « باتكلا ةجمرت في ءاطخلأا ليلتح ةلاقلما هذه تلواح .تاجمترلما ةيطايتحلاا ةجمترلا عون ميدقتو ةجمترلا في ةعقاولا ءاطخلأا ىلع روثعلا ثحابلا لواح ،ةساردلا هذه في .ينمأ عقوم بيترت في تناك فدلها ةغللا في لملجا بيكارت ءاطخأ نأ يه ةساردلا هذه جئاتنو .ءاطخلأا هذله ةداعإو هتجمرت لىإ جاتيح لا تيلا صنلا ةجمرت في نوكت ،ةلاّ عفلا لملجا مادختسا في ءاطخلأا امأ .لملجا ةغللا في – ةفدارلما تاملكلا رايتخا في ءاطخلأا لمشت تاملكلا ةجمرت في ءاطخلأاو .اقباس ةروكذلما تاملكلا ،تاملكلا فذح بنالجا في كلذكو ،ةيحلاطصلاا تارابعلا ةجمرت في ءاطخلأاو ،ةبسانلما يرغ – فدلها .لملجاو بيكاترلاو